Penerapan Strategi Problem Based Learning dalam Meningkatkan Motivasi Belajar Siswa pada Pendidikan Agama Kristen (Jurnal Sosial Humaniora dan Pendidikan, 2023)
The learning process in the classroom until now there are still teachers who position students as learning objects because students only listen to the material delivered by the teacher in front of the class as the main source of learning and the method used by the teacher mostly uses the lecture method, so it's easy for students to feel bored with the material given because it is less interesting. The problem-based learning model is different from other models because the teacher's role is to present students with a problem that exposes students to be active in solving problems. So the teaching and learning process using the Problem Based Learning model is the right choice in formulating problem-based learning. The purpose of writing this article is to assist students in developing inquiry and problem solving skills because solving problems has a real world context. Where giving these problems faced students in groups to have innovative skills and student motivation in learning.